Hakikat Pemikiran Seyyed Hossein Nasr - Mumtaz, Nadhif Muhammad (JURNAL INDO-ISLAMIKA, 2014)
This study wants to provide insight into the importance of thinking Seyyed Hossein Nasr in the Islamic world. The rise of various thoughts that deviate from the teachings of Islam made Seyyed Hossein Nasr moved to make breakthroughs in reforms that denied in the Islamic world. One response that challenges the thought of Seyyed Hossein Nasr is the flow of Western development that overrides the spiritual aspect. Seyyed Hossein Nasr is due to the opposition to the Islamic religion which is felt to be very struggling with Islamic civilization going forward. The main weapon of Seyyed Hossein Nasr to counter this Western discussion is the use of the philosophy of perennialism or what is often referred to as Pernenis Religion.